Reconfiguring Pesantren Education: The Dialectic between Tradition, Modernity, and Transnational Islam - Jemmy Harto; Setiawan, Dede; Asep Saepuddin; Hudalloh; Muhammad Asyraf (Fakultas Keguruan dan Ilmu Pendidikan Universitas Nahdatul Ulama Indonesia, 2025)
The pesantren, as Indonesia’s oldest Islamic educational institution, has long been central to shaping the religious and socio-cultural identity of Muslim communities. In Banten, pesantren represent deep traditional roots linked to the intellectual legacy of prominent scholars such as Shaykh Nawawi al-Bantani. Yet, the pressures of globalization and the influence of Islamic reform movements have positioned pesantren at the intersection of competing discourses—traditionalist, modernist, and transnational. This study explores the dialectical challenges encountered by pesantren in Banten as they negotiate among these currents. Using a qualitative approach that combines literature review and selected case studies, the research reveals the dynamic strategies employed by traditionalist pesantren to preserve classical Islamic learning while accommodating modern educational demands. Modernist pesantren, in turn, advocate for rationalism, curricular innovation, and the integration of secular sciences, though not without resistance from traditionalists. Meanwhile, transnational Islamic movements such as Salafism, Hizb ut-Tahrir, and Tablighi Jamaat introduce alternative notions of orthodoxy and authority. The study concludes that pesantren in Banten are undergoing a continuous process of negotiation that redefines their identity, demonstrating both resilience and adaptability in a rapidly globalizing Islamic context.